2008
DOI: 10.1016/j.immuni.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-Editing Enzyme A20 Restricts Nucleotide-Binding Oligomerization Domain Containing 2-Triggered Signals

Abstract: Muramyl dipeptide (MDP), a product of bacterial cell-wall peptidoglycan, activates innate immune cells by stimulating nucleotide-binding oligomerization domain containing 2 (NOD2) -dependent activation of the transcription factor NFkappaB and transcription of proinflammatory genes. A20 is a ubiquitin-modifying enzyme that restricts tumor necrosis factor (TNF) receptor and Toll-like receptor (TLR) -induced signals. We now show that MDP induces ubiquitylation of receptor- interacting protein 2 (RIP2) in primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
251
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(262 citation statements)
references
References 51 publications
11
251
0
Order By: Relevance
“…Coexpression of A20, an enzyme known to counter-regulate Nod2 signaling by deubiquitinating RIP2 (ref. 43), abrogated the Pellino3-mediated ubiquitination of RIP2 (Fig. 5a).…”
Section: Pellino3 Ubiquitinates Rip2mentioning
confidence: 89%
“…Coexpression of A20, an enzyme known to counter-regulate Nod2 signaling by deubiquitinating RIP2 (ref. 43), abrogated the Pellino3-mediated ubiquitination of RIP2 (Fig. 5a).…”
Section: Pellino3 Ubiquitinates Rip2mentioning
confidence: 89%
“…They recognize peptidoglycan structure of pathogens. Recognition by NLRs induces selfoligomerization of NLRs and actiavates NF-κB and MAPK (Park et al, 2007;Hasegawa et al, 2008;Hitotsumatsu et al, 2008), which subsequently results in the release of IL-1 family of cytokines including IL-1 , IL-18, and IL-33 (Meylan et al, 2006;Fritz et al, 2006;Ting et al, 2006;Kanneganti et al, 2007;Yu & Finlay, 2008). There is feasible evidence supporting that NLRs play a role in the pathogenesis of autoimmune diseases.…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…In addition to regulating TNF-induced RIP ubiquitylation, A20 restricts TLR-induced NF-B signals by deubiquitylating the E3 ligase TRAF6 (9,11). A20 also dampens NOD1-and NOD2-induced NF-B signals by deubiquitylating RIP2, possibly preventing it from recruiting IKK to the signaling complex (10). Hence, like other DUBs and E3 ligases, A20 regulates the ubiquitylation of multiple protein targets.…”
Section: The Mechanics Of A20 Actionmentioning
confidence: 99%
“…Epistasis experiments revealed that genetic deletion of TNF or TNF receptor 1 (TNFR1) in A20-deficient mice did not rescue the mice from premature death, demonstrating that A20 regulates proinflammatory signals in addition to TNF (9). We now know that A20 also restricts NF-B signaling in response to stimulation of the TLR and NOD pathways (9,10). A20 regulates innate immune homeostasis independently of adaptive immune cells, as A20 / RAG-1 / mice lacking mature T and B cells develop severe spontaneous inflammation and perinatal death (8).…”
mentioning
confidence: 99%